Livestock production land and conservation areas play a complementary role in the conservation of a critically endangered grassland bird - Daniel T. Nugent; David J. Baker‐Gabb; Mark Antos; Luke Collins; Peter Green; John W. Morgan (Ecological Solutions and Evidence, 2022)
Abstract In many parts of the world, livestock production and biodiversity conservation are important land uses of native grasslands in agricultural landscapes. Approaches to managing grasslands typically differ between production farms and conservation areas as they have different goals. Such differences may have consequent effects on the spatial and temporal habitat suitability for grassland fauna. In semi‐arid grasslands of south‐eastern Australia, the critically endangered Plains‐wanderer (Pedionomus torquatus) is a grassland habitat‐specialist bird that can occur on land managed for livestock production and conservation, but it is unclear if, and when, habitat suitability is affected in each land‐use type. Here, we investigate how land‐use type (livestock production, conservation) and rainfall (preceding accumulated rainfall) affect habitat suitability for the Plains‐wanderer using 11 years of bird occurrence and remotely sensed habitat structure data. We found habitat suitability for the Plains‐wanderer was driven by an interaction between land use and rainfall, with conservation areas supporting larger areas of preferred habitat structure during dry periods but less during wet periods. By contrast, Plains‐wanderers were more likely to occur on livestock production farms during wet periods. We speculate this is because higher grazing pressure on livestock production farms was able to limit biomass accumulation and, hence, maintain more areas of preferred habitat structure. Our findings show that land used for livestock production can complement conservation areas by providing preferred habitat for the Plains‐wanderer during climatic periods that promote grass growth. Furthermore, we highlight that land use and climate are important temporal drivers of grassland dynamics, and approaches to biodiversity conservation should consider how patterns of habitat suitability may shift across landscapes over time. Strategic, landscape‐scale planning and effective agri‐environmental initiatives will be critical to the future of grassland birds such as the Plains‐wanderer.